Implementar la Metodología de las Mejoras Enfocadas (16 Grandes pérdidas) para la sección de Subdivisión y empaque de la empresa STEIN CORP - Martínez-Hernández, Andrey Gerardo (Instituto Tecnológico de Costa Rica, 2017)
The project aims to increase the availability delivered by the Engineering Department to the Subdivision and packaging section of the STEIN CORP, Cartago plant. By decreasing the large losses defined by the TPM. For this purpose, an analysis was made with a managerial approach of the 16 major losses of the TPM, which resulted in the problems of initial adjustments as the main cause of hours of unemployment in the equipment. Then a criticality analysis was developed to determine the production lines that most affected the availability of the section. With this, it was discovered that the blister EM 5010, the liquid filler EM 3012 and the encelofanadora Satellite EM 9005. They are the equipment that most reduced this indicator and that its stoppage entailed the stoppage of secondary equipment of the line. In accordance with the interests of STEIN CORP, visual control improvements are developed for these teams and jointly with the technical team to obtain procedures that optimize the process of the initial adjustments of the equipment. For this, the SMED methodology is used, which allows to reduce unemployment times from 30 to 40%. The improvements raised generate an increase in the availability of the section of 4% and a saving of 1.614.400 colons. It is expected that the less critical teams of the Section will continue to grow with the continuation of the project.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: TPM; Metodología SMED; Análisis; Control; Pérdidas; Research Subject Categories::TECHNOLOGY::Engineering mechanics